2017
DOI: 10.25258/ijpapr.v9i1.8046
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Total Phenolic, Flavonoid and Carotenoid Content of Sesbania sesban (L. Merr) Leaves Extract with DPPH Scavenging Activties

Abstract: Antioxidants are found in many plants and can neutralize free radicals. Sesbania sesban (L.)Merr is a plant that has been used empirically by Indonesian people and its proven have many pharmacologycal activity. The objectives of this research were to study antioxidant activity Sesbania sesban leaves extract using DPPH (2,2-diphenyl-1-picrylhydrazyl) method and correlation with its total phenolic, flavonoid and carotenoid content. Extraction was performed by reflux using different polarity solvent. The extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 0 publications
3
9
1
5
Order By: Relevance
“…Biosintesis dan Tabel 2. Hasil analisis kimia terhadap tepung labu kuning madu pada berbagai umur panen (15,20,25, dab 30 hari setelah terbentuknya bakal buah) Table 2. The results of chemical analysis on maturity stage factor of honey pumpkin flour at various harvest age (15, 20, 25, Tabel 3.…”
Section: Total Karotenoidunclassified
“…Biosintesis dan Tabel 2. Hasil analisis kimia terhadap tepung labu kuning madu pada berbagai umur panen (15,20,25, dab 30 hari setelah terbentuknya bakal buah) Table 2. The results of chemical analysis on maturity stage factor of honey pumpkin flour at various harvest age (15, 20, 25, Tabel 3.…”
Section: Total Karotenoidunclassified
“…A correlation analysis was performed on total phenolics and flavonoids contents using Pearson's correlation coefficient. Pearson's correlation coefficient was positively high if 0.610 < r < 0.974 and negatively high if -0.610 < r < -0.974 33 . As expected, total phenolics content of CrE and fractions had strong positive correlation with flavonoids content (r = 0.893).…”
Section: Total Phenolics and Flavonoids Contentsmentioning
confidence: 99%
“…This can be supported from previous studies conducted by Rohmah et al, (2018) on acetone extract of leaves and stems of white Turi (Sesbania grandiflora) have antioxidant power with IC 50 values of 56.5707 ppm and 54.2608 ppm. Besides, the type of yellow Turi, namely ethanol extract of yellow Turi leaf, has antioxidant power with an IC 50 value of 4.12 ppm (Fitriansyah et al, 2017). Likewise, Sesbania sesban leaves extracts with different polarity solvents (n-hexane extract, ethyl acetate extract and ethanol extract) can be categorized as very strong antioxidant.…”
Section: Test Substancesmentioning
confidence: 99%
“…The research of (Fitriansyah et al, 2017) showed that extracts of n-hexane, ethyl acetate, and ethanol of Sesbania sesban (L. Merr) leaves had an IC 50 DPPH antioxidant activity <50 μg / mL and could be classified as a very strong antioxidant. Sesbania Sesban ethanol extract has the highest total phenolic content (5.18 g GAE / 100 g) and the highest total flavonoid content (4.56 g QE / 100 g), while the highest total carotenoid content (4.56 g BE / 100 g) in n-hexane extract.…”
Section: Introductionmentioning
confidence: 99%